Does the Conduct of Critical Thinking Add to the Impact Higher-Educated Young Professionals Make? - de Graaf, Boudewijn (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation investigates whether the conduct of Critical Thinking (CT) enhances the Impact that higher-educated Young Professionals (YPs) make at the start of their careers. While CT is widely promoted in the curricula of higher education institutes (HEIs), little research was available if CT, conducted by YPs really results in making Impact. This study introduces a new conceptual model integrating CT, Mental Models, and Impact. A perception-based survey including a custom CT ability test among 29 Dutch HEI graduates and 11 of their managers measured the CT-ability, behavioral conduct and Impact of YPs. Results reveal a statistically significant, strong correlation between Friendly Voiced outward-directed CT conduct—not merely CT ability—and positive Impact. Findings suggest that developing CT conduct early during higher education and incorporating the development of Friendly Voiced outward-directed CT through application in later years of higher education through real-life assignments can substantially enhance a YP's effectiveness. Additionally, discrepancies were found between YPs’ perceived freedom to exercise CT and managers' assumptions, indicating that organizations could foster greater Impact by mentoring and encouraging Friendly Voiced outward-directed CT behavior. The research offers practical recommendations for higher education institutions and employers and calls for further exploration into longitudinal effects and broader organizational contexts.